2021
DOI: 10.31083/j.rcm2204163
|View full text |Cite
|
Sign up to set email alerts
|

Altered circulating marinobufagenin levels and recurrent intradialytic hypotensive episodes in chronic hemodialysis patients: a pilot, prospective study

Abstract: Intradialytic hypotension (IDH) is a sudden and often serious complication of chronic hemodialysis (HD). In this prospective study, we aimed at evaluating the clinical predictors of IDH in a homogeneous cohort of chronic HD patients, with a particular focus on marinobufagenin (MBG), an endogenous cardiotonic steroid which alterations have previously been involved in various cardiovascular disorders. MBG levels in HD patients were significantly higher than in controls (p = 0.03), remained unchanged throughout a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Consistent with a previous study 9 , our results showed that HD patients who were over 65 years old and with a higher CCI index level had higher risks of IDH. Midodrine is the most commonly used vasopressor, and the more it is used, the higher the number of IDH episodes in dialysis patients 25 . In our study, 30.9% of HD patients used midodrine, and its prescription rate was higher in CHM non-users than in CHM users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with a previous study 9 , our results showed that HD patients who were over 65 years old and with a higher CCI index level had higher risks of IDH. Midodrine is the most commonly used vasopressor, and the more it is used, the higher the number of IDH episodes in dialysis patients 25 . In our study, 30.9% of HD patients used midodrine, and its prescription rate was higher in CHM non-users than in CHM users.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus de nition of IDH; however, current de nitions based on symptoms and/or interventions are clinically relevant 9 . Vasopressors are usually administered to prevent and control hypotension episodes during HD 25 . This is why our study used vasopressors to correlate the incidence of hypotension in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Na/K-ATPase signaling is another major driver of pathological cardiac fibrogenesis. This holds true particularly in UCM, in which a hyperstimulation of this pump is triggered by endogenous steroids, such as marinobufagenin (MBG), which accumulates in the bloodstream as uremic toxins [ 34 , 35 ]. Na/K-ATPase signaling involves downstream signaling proteins, such as Src [ 36 ], Akt and PKCs [ 37 ], which culminate in the enhancement of various pro-fibrotic pathways [ 38 ].…”
Section: Mirnas Ucm and The Na/k-atpase Signaling Pathwaymentioning
confidence: 99%
“…The kidney plays a key role in maintaining systemic MBG balance by regulating urinary excretion [ 3 ]. Hence, not surprisingly, MBG accumulates in the blood of anuric individuals necessitating chronic dialysis [ 6 , 7 , 8 ], while in kidney transplant recipients, higher circulating MBG levels be associated with the severity of the graft function impairment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%